Bizancjum jako ideał skazany na unicestwienie i sensotwórcza miłość w cyklu poetyckim O dziełach miłości albo Bizancjum Ivana V. Lalicia - Maszkiewicz, Magdalena (Slavia Occidentalis, 2017)
The goal of this article is to interpret the two motifs indicated in the title which intertwine in the poetic series Of the Works of Love, or Byzantium by Ivan V. Lalić, a Serbian poet. Perception of Byzantium as a reality which, having reached perfection, is annihilated and of love as a meaning-giving category connects with a coherent vision in the author’s entire work. The reflections presented in this article provide an impetus to comprehend the series in question, and Lalić’s entire poetry.